'Gamma Anna': a classroom demonstration for teaching the concepts of gamma imaging. (1st November 2016) - Wolff, Nicola; Griffiths, Jennifer; Yerworth, Rebecca
Abstract: Gamma imaging is at the interface of medicine and physics and thus its teaching is important in both fields. Pedagogic literature highlights the benefits of interactive demonstrations in teaching: an increase in enjoyment and interest, as well as improvement in academic achievement. However gamma imaging uses radioactive sources, which are potentially dangerous and thus their use is tightly controlled. We have developed a demonstration which uses a localised exothermic reaction within a rag doll as an analogue of radioactivity. This can be safely used in classrooms to demonstrate the principles of gamma imaging. The tool is easy to make, cheap, robust and portable. The supplementary material in this paper gives teacher notes and a description of how to make the rag doll demonstrator. We have tested the tool using six participants, acting as 'teachers', who carried out the demonstration and described the doll as easy to use, and the 'tumour' clearly identifiable. The teaching tool was separately demonstrated to a group of 12 GCSE physics students and a group of 12 medical students. Feedback showed increased student engagement, enjoyment and understanding of gamma imaging. Previous research has shown that these benefits have an impact on learning and academic outcomes.